2019
DOI: 10.3389/fphar.2019.00389
|View full text |Cite
|
Sign up to set email alerts
|

Baishouwu Extract Suppresses the Development of Hepatocellular Carcinoma via TLR4/MyD88/NF-κB Pathway

Abstract: Purpose: The root of Cynanchum auriculatum Royle ex Wight, known as Baishouwu, has been widely used for a tonic supplement since ancient times. The current study was performed to explore the effect of Baishouwu extract on the development of experimental hepatocellular carcinoma (HCC) and the potential mechanism involved. Methods: Rats were injected diethylnitrosamine (DEN) to initiate the multistep hepatocarcinogenesis. Animals were treated concurrently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…HCC (Kang et al, 2018;Ding et al, 2019;Zhang et al, 2020). The inhibition of the TLR4/MyD88 pathway represses the occurrence and progression of HCC (Ding et al, 2019;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HCC (Kang et al, 2018;Ding et al, 2019;Zhang et al, 2020). The inhibition of the TLR4/MyD88 pathway represses the occurrence and progression of HCC (Ding et al, 2019;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…HCC (Kang et al, 2018;Ding et al, 2019;Zhang et al, 2020). The inhibition of the TLR4/MyD88 pathway represses the occurrence and progression of HCC (Ding et al, 2019;Zhang et al, 2020). NF-κB-mediated EMT process contributes to HCC progression, and the suppression of the NF-κB pathway represses EMT and invasion of tumor cells (Song et al, 2014;Zhu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Song, Liu, & Yu, 2020). On the contrary, Toll‐like receptor 4 (TLR4)/MyD88 plays a significant role in inflammation and enhances the malignancy and proliferation of different cancers (Ding, Peng, Ding, & Peng, 2019; Koliaraki et al, 2019). Both EGFR and TLR4 can act as upstream mediators to stimulate epithelial‐to‐mesenchymal transition (EMT) in cancer cells, leading to their malignant behavior (Y. Cao, Shen, Zhang, Zhang, & Zhang, 2019; Shao et al, 2019).…”
Section: Curcumin and Lung Cancermentioning
confidence: 99%
“…In the Chinese and Korean pharmacopeia, the tuberous root of C. auriculatum named "Baishouwu" or "Baekshuoh" has been used as a traditional herbal medicine to treat gastric ulcers, neurasthenia, edema and nephritis [2,3]. Pharmacological and phytochemical studies have reported that C. auriculatum has high application and economic value and displays beneficial antiviral [4], gastroprotective [5], antioxidant [6], antidepressant [7] and antitumor activities [8]. Caudatin is a type of C-21 steroid mainly isolated from C. auriculatum, which has been shown to have effective activity against cancers of different origins [9,10].…”
Section: Introductionmentioning
confidence: 99%